Structural robustness of China’s UAV enterprise network: a national and provincial analysis based on business homogeneity - Zhang, Xuemei; Guo, Jianfeng; Liu, Siyao (Frontiers in Physics, 2025)
IntroductionThe rapid growth of the unmanned aerial vehicle (UAV) market has surged enterprises, exposing them to systemic risks from business homogeneity. This issue has spread not only within the same level of the industrial chain but also across different segments. Despite China’s enterprises spanning the entire chain as the largest market, their business structure and regional differences remain largely unexplored.MethodThis study constructs a three-tier UAV enterprise network based on overlapping business scopes among firms, forming upstream, midstream, and downstream layers, and examines its national and provincial structural robustness through topological characteristics and network dismantling experiments.ResultsThe results reveal that national- and provincial-level UAV enterprise networks follow a power-law distribution, reflecting a “rich-get-richer” pattern. The national network is less robust than the provincial average, with downstream segments in delivery, agriculture, and other applications particularly vulnerable. Provincial networks exhibit strong regional heterogeneity; economically developed provinces demonstrate stronger internal coordination but are more fragile due to high centralization. Furthermore, provincial networks fall into four structural types with differing levels of efficiency and robustness.DiscussionThe study highlights how business similarity fosters local coordination but increases systemic risk through structural homogeneity. To enhance network resilience, especially in downstream and centralized regions, strategies such as modular design and region-specific coordination are essential.